GAN BAO'S «IN SEARCH OF THE SUPERNATURAL: THE WRITTEN RECORD» AS A KEY TO THE СHINESE MEDIEVAL WORLDVIEW - Shcherbakov , Yaroslav (Collection of scientific papers «ΛΌГOΣ», 2024)
The "Dark Ages" in the world history and in China. Human history is built on numerous paradoxes. The "Dark Ages" of the early Middle Ages where exactly the era that replaced antiquity. But in the history of the Eurasian continent, it was this new era, about which we know the least due to the lack of written records, that brought the greatest changes in human life. After all, we are talking about the period when the medieval Christian civilization, the civilization of the Far East, and later the civilization of Islam were born.